Expanding Training Opportunities for Parents of Children with Autism. (September 2014) - Suppo, Jennifer L.; Mayton, Michael R.
The purpose of this study was to demonstrate that parents who have children diagnosed with autism can learn and accurately apply knowledge regarding a research-based practice for their children by utilizing a prescribed, self-directed, online program. Using a quasi-experimental, non-equivalent control group, pretest-posttest design, this study assessed (a) parent knowledge of visual supports, (b) creation of an appropriate visual support, and (c) social validity regarding the program. Results demonstrated that parents who receive training using an online program can accurately apply a research-based practice, and participant feedback indicated strong satisfaction with this method of obtaining and applying knowledge. Results suggested that using a self-directed, online program may serve to give families another method of obtaining informational support and training and thereby address some of the need made more urgent by lacking or delayed services for their children with autism.